2004
DOI: 10.1002/mpr.171
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel investigation of variation in HoNOS ratings by mental health professionals: a naturalistic study of consecutive referrals

Abstract: Episodes of mental healthcare in specialist psychiatric services often begin with the assessment of clinical and psychosocial needs of patients by healthcare professionals. Particularly for patients with complex needs or severe problems, ratings of clinical and social functioning at the start of each episode of care may serve as a baseline against which subsequent measures can be compared. Currently, little is known about service variations in such assessments on referrals from primary care. We set out to quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…In terms of making ratings as accurate and consistent as possible for both clinical and research use; some recent research has suggested that there may be differences in the perceptions of, and ratings made by, people from different professional backgrounds (Davies et al, 2006), due to differences in their clinical frames of reference, any specialist training received and levels of experience. Ecob et al (2004) suggest the need for specialized training to address any adjustments required to counter such effects. Due to the additional complexities of FMHSUs, and addressing identifi ed needs within the wider framework of risk and accountability (Andrews and Bonta, 2003;Cohen and Eastman, 2000), some formalized training about how to score CANFOR may address some of the differences between raters, and lead to greater consistency and therefore practical utility.…”
Section: Test-retest Reliabilitymentioning
confidence: 97%
“…In terms of making ratings as accurate and consistent as possible for both clinical and research use; some recent research has suggested that there may be differences in the perceptions of, and ratings made by, people from different professional backgrounds (Davies et al, 2006), due to differences in their clinical frames of reference, any specialist training received and levels of experience. Ecob et al (2004) suggest the need for specialized training to address any adjustments required to counter such effects. Due to the additional complexities of FMHSUs, and addressing identifi ed needs within the wider framework of risk and accountability (Andrews and Bonta, 2003;Cohen and Eastman, 2000), some formalized training about how to score CANFOR may address some of the differences between raters, and lead to greater consistency and therefore practical utility.…”
Section: Test-retest Reliabilitymentioning
confidence: 97%
“…HoNOS-D) were administered by clinicians following their initial contact with the patients during the fi rst week and the last week of inpatient treatment, just before the patients' discharge. Ecob et al (2004) pointed out that investigations of HoNOS scores must take possible interrater variation into account. In order to control for this aspect, the same clinician completed all of the clinicianrated instruments for one specifi c patient both at admission and discharge.…”
Section: Design and Settingmentioning
confidence: 99%
“…Nevertheless, many measurement tools have been developed. These measurement tools are often administered by interviewers or raters rather than being completed by the patient (Ecob et al ., ). The Positive and Negative Symptom Scale (PANSS) is an example of a scale in which interviewers rate the severity of patient symptoms.…”
Section: Introductionmentioning
confidence: 97%